Conservation importance of wetlands for faunal diversity (Zoological Records and Reviews, 2024)
Wetlands are among the most biodiverse and ecologically productive ecosystems on Earth, yet they continue to be lost at rates three times higher than forests globally. This study quantifies the conservation importance of wetlands for faunal diversity across four wetland types -- natural fens, managed reedbeds, restored peatlands, and floodplain forests -- in Sweden, Denmark, and the Netherlands, using multi-taxon biodiversity surveys (waterbirds, macroinvertebrates,amphibians, dragonflies; n = 16,847 individual records across 284 taxa) at 54 wetland sites of varying condition andmanagement history (2021-2023). Wetland condition index (WCI, 0-100) was the strongest predictor of multi-taxonspecies richness across all four taxonomic groups (linear mixed model beta = 0.58 +- 0.07, p < 0.001). Natural fenssupported the highest mean species richness across all groups (waterbirds 18.4 +- 2.1 species, amphibians 5.8 +- 0.9,dragonflies 24.8 +- 3.2, macroinvertebrates 42.4 +- 4.8), while degraded peatlands showed the greatest depletionsrelative to near-natural reference conditions. Functional diversity (FRic) was positively correlated with WCI (r = 0.74, p